The Use and Need of the Life of Carry A. Nation - Nation, Carry Amelia, 1846-1911 (Salt Lake City, UT : Project Gutenberg, 1998)
"The Use and Need of the Life of Carry A. Nation" by Carry Amelia Nation is a memoir written in the early 20th century, reflecting on the author$1 (Bs life experiences and advocacy work. The book focuses on Carry Nation's fervent activism against alcohol and the societal issues surrounding it, using her personal narrative as a lens to highlight the struggles and triumphs she faced, particularly as a woman in a predominantly male-dominated society. At the start of the memoir, Carry Nation reflects on her early life in Kentucky, providing vivid details about her childhood home, family dynamics, and the cultural context of the time. She shares fond memories of her family's plantation, particularly her interactions with the enslaved people on the estate, and discusses the values instilled in her by her father. As she transitions into her life as a young woman, she begins to grapple with issues of marriage and domestic hardship, revealing her deep empathy for the struggles faced by women, especially those affected by alcohol and societal neglect. The opening chapters establish a foundation for her later activism by illustrating the personal impact of alcohol on families and communities, ultimately setting the stage for her life's work in promoting temperance and women's rights. (This is an automatically generated summary.)s
Release date is 1998-10-01
Scanned by Charles Keller for Sarah with OmniPage Professional OCR software
Keywords: Social reformers -- United States -- Biography; Nation, Carry Amelia, 1846-1911; Temperance -- United States